2018
DOI: 10.1021/acsami.8b01970
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Pt Nanoparticles and Amorphous Nickel Supported on 3D Mesoporous Carbon Derived from Cu-Metal–Organic Framework for Efficient Methanol Oxidation and Nitrophenol Reduction

Abstract: The development of novel strategy to produce new porous carbon materials is extremely important because these materials have wide applications in energy storage/conversion, mixture separation, and catalysis. Herein, for the first time, a novel 3D carbon substrate with hierarchical pores derived from commercially available Cu-MOF (metal-organic framework) (HKUST-1) through carbonization and chemical etching has been employed as the catalysts' support. Highly dispersed Pt nanoparticles and amorphous nickel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…The red curve in Figure a shows that the catalytic activity of the Ni 0.6 Co 0.4 alloy (116 mA cm −2 ) is clearly better than those of single nickel and cobalt metals (black and blue curves) and indicates a good synergistic effect between Ni and Co with appropriate ratio. The Ni atoms tend to lengthen the C−O bond length in the methanol molecule, which also can be easily absorbed by NiOOH mainly because of its empty d orbital or unpaired electrons . Although cobalt does not have the effect of oxidizing methanol (blue curve in Figure a), it still plays an important role in Ni x Co 1− x .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The red curve in Figure a shows that the catalytic activity of the Ni 0.6 Co 0.4 alloy (116 mA cm −2 ) is clearly better than those of single nickel and cobalt metals (black and blue curves) and indicates a good synergistic effect between Ni and Co with appropriate ratio. The Ni atoms tend to lengthen the C−O bond length in the methanol molecule, which also can be easily absorbed by NiOOH mainly because of its empty d orbital or unpaired electrons . Although cobalt does not have the effect of oxidizing methanol (blue curve in Figure a), it still plays an important role in Ni x Co 1− x .…”
Section: Resultsmentioning
confidence: 99%
“…The Ni atoms tend to lengthent he CÀOb ond length in the methanol molecule,w hich also can be easily absorbedb yN iOOH mainly because of its empty do rbitalo ru npaired electrons. [57] Although cobalt does not have the effect of oxidizing methanol (blue curve in Figure 5a), it still plays an important role in Ni x Co 1Àx .F irst, the conductivity of Co(OH) 2 in solution is better than that of Ni(OH) 2 ,w hich is beneficialt o electron transport. [64] Additionally, absorption of CO and the intermediate products on cobalt can greatly facilitate their furthero xidation by Ni 3 + and decrease the CO poisoningo f Ni.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar structure of pristine Ni/Zn‐MOF (Figures S4 and S5) suggests that the encapsulation of Pt NPs did not damage the structure of Ni/Zn‐MOF, in agreement with the PXRD result. Importantly, the yolk–shell structure of the MOF and a clear cavity between the outer shell and inner yolk sphere were further revealed by TEM (Figure D), in which the Pt NPs with exposed (111) plane are uniformly distributed (Figure S6) . Furthermore, the energy‐dispersive X‐ray spectroscopy (EDS) mapping analysis of Pt void @MOF(Y) showed that the Zn, Ni, and Pt elements in Pt void @MOF(Y) are homogeneously distributed on the Echinoidea‐like structure (Figure E).…”
Section: Methodsmentioning
confidence: 94%
“…Importantly,t he yolk-shell structureo ft he MOF and ac lear cavity between the outer shell and inner yolk sphere were furtherr evealed by TEM ( Figure 1D), in which the Pt NPs with exposed (111)p lane are uniformly distributed (Figure S6). [10] Furthermore, the energy-dispersive X-ray spectroscopy (EDS) mapping analysis of Pt void @MOF(Y) showed that the Zn, Ni, and Pt elements in Pt void @MOF(Y) are homogeneously distributed on the Echinoidea-like structure ( Figure 1E). Thus, the spatial distribution of incorporated Pt NPs in/on the MOF can be controlled by their addition sequence.…”
mentioning
confidence: 99%